2008
DOI: 10.1136/adc.2008.147587
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide concentrations to guide treatment of patent ductus arteriosus

Abstract: BNP-guided treatment reduced the number of primary indomethacin doses. There was no increase in PDA persistence or associated morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Problems with sample handling and different assay characteristics for BNP and pro-BNP can alter measurements, and the absolute value has less significance than the trend. [138][139][140][141][142][143][144] As in adult PAH, increased levels of atrial natriuretic peptide, troponin T, 145 and uric acid 146,147 correlate with poor short-term outcome in older children and adolescents. …”
Section: Biomarkersmentioning
confidence: 99%
“…Problems with sample handling and different assay characteristics for BNP and pro-BNP can alter measurements, and the absolute value has less significance than the trend. [138][139][140][141][142][143][144] As in adult PAH, increased levels of atrial natriuretic peptide, troponin T, 145 and uric acid 146,147 correlate with poor short-term outcome in older children and adolescents. …”
Section: Biomarkersmentioning
confidence: 99%
“…The value of the BNP/NT-proBNP measurement in serum to diagnose hsPDA and to monitor therapy was shown in various studies [7][8][9] . Some of these studies have shown differences in protein concentrations in serum of neonates with and without hsPDA, as well as the decrease of protein concentrations after closure of the ductus [8,9] .…”
Section: Discussionmentioning
confidence: 99%
“…Decreased protein concentrations of BNP and NT-proBNP were observed after successful closure of the ductus [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…BNP can be used to differentiate preemies with and without a patent ductus arteriosus (PDA) as well as potentially guide therapy. Attridge et al[17] showed that by using BNP, fewer doses of indomethacin were used for therapy of PDA. Of note, the pediatric heart can compensate better with pressure overload than volume overload and this can directly impact BNP secretion or level.…”
Section: B-type Natriuretic Peptide and N-terminal Segment Of Pro-b-tmentioning
confidence: 99%